Financial market volatility and maritime freight indices: A connectedness approach - Tarkun, Savas (Elsevier, 2025)
This study investigates the dynamic and time-varying connectedness between global financial markets and maritime freight indices, emphasizing the transmission and direction of volatility shocks during periods of economic uncertainty. Using the Connectedness Decomposition Approach (TVP-VAR-based), we explore the interaction between major global stock indices (e.g., S&P 500, DJIA, DAX, NIKKEI225) and maritime freight indicators (BDI, BDTI, BCTI) over the period from January 2013 to December 2024. Our results reveal that stock market volatility significantly influences shipping indices, especially during global crises such as the COVID-19 pandemic. However, freight indices are not merely passive receivers of financial shocks; in certain episodes, they act as net transmitters of volatility, affecting financial markets in return. This dual behavior indicates a structural shift in the maritime sector's role within the global economic system. Furthermore, the findings show a declining trend in total connectedness post-2016, reflecting increased segmentation between freight and financial markets. These insights are particularly valuable for policymakers, investors, and maritime stakeholders seeking to develop hedging strategies, strengthen supply chain resilience, and better forecast market dependencies during financial and geopolitical turmoil.
Keywords: Financial market shocks; Maritime freight indices; Spillover effects; Connectedness decomposition; Economic crises